2005
DOI: 10.1103/physrevb.72.094419
|View full text |Cite
|
Sign up to set email alerts
|

Raman response of magnetic excitations in cuprate ladders and planes

Abstract: An unified picture for the Raman response of magnetic excitations in cuprate spin-ladder compounds is obtained by comparing calculated two-triplon Raman line-shapes with those of the prototypical compounds SrCu2O3 (Sr123), Sr14Cu24O41 (Sr14), and La6Ca8Cu24O41 (La6Ca8). The theoretical model for the two-leg ladder contains Heisenberg exchange couplings J and J ⊥ plus an additional four-spin interaction Jcyc. Within this model Sr123 and Sr14 can be described by x := J /J ⊥ = 1.5, xcyc := Jcyc/J ⊥ = 0.2, J Sr123… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 80 publications
1
14
0
Order By: Relevance
“…70,71 As the coupling between the magnons increases, the peak approaches the lower band edge. [69][70][71] Turning to the ladder with Dzyaloshinskii-Moriya interaction, in the weak-coupling case, the threshold at twice the spin gap will be obtained from the contribution of antisymmetric modes a / a to the Raman intensity. 67 The symmetric modes will give extra peaks and thresholds but at energy scales small compared to the gap.…”
Section: Raman Scattering Intensitymentioning
confidence: 99%
“…70,71 As the coupling between the magnons increases, the peak approaches the lower band edge. [69][70][71] Turning to the ladder with Dzyaloshinskii-Moriya interaction, in the weak-coupling case, the threshold at twice the spin gap will be obtained from the contribution of antisymmetric modes a / a to the Raman intensity. 67 The symmetric modes will give extra peaks and thresholds but at energy scales small compared to the gap.…”
Section: Raman Scattering Intensitymentioning
confidence: 99%
“…A longstanding source of uncertainty for Sr 14 Cu 24 O 41 has been the intense high-energy spectral weight. 28 Gozar et al 29 in a study focused primarily on the two-magnon response have observed the transfer of spectral weight from the low-energy ͑Ͻ700 cm −1 ͒ region of their Raman spectra to higher energy as T is decreased. The disappearance of low-energy continuum states on cooling has also been observed Sugai and Suzuki.…”
Section: Resultsmentioning
confidence: 97%
“…Using this modulation one can explain the disappearance of the one-triplon excitation at q x = 0, and the emergence at q x 0. Both in Raman [39] and RIXS [68] experiments, finite two-triplon excitation intensity is observed in spin ladders at zero momentum transfer. According to Eqs.…”
Section: A K-edge Rixsmentioning
confidence: 98%